The Effect of Potassium Sorbate on Microorganism and Self life of Laboratory Biscuit (Baghdad Science Journal, 2025)
This study has been conducted to examin the effect of potassium sorbate at different level of 0.03,0.06,0.10% on the number of bacteria and mold and to extend the storage life of laboratory processed biscuit.The results indicated that the use of 0.03% potassium sorbate prolonged the storage peroid until the third month .three types of bacteria has been isolated from processed biscuit, namely, Staphylococcus aureus, Bacillus cereus, Esherichia coli using 0.06% potassium sorbate showed no growth of bacteria up to six month of storage ,while using of 0.03% and 0.06% potassium sorbate prevent the growth of mold up to three and six months of storage respectively. Both Aspergillus and Penicillium were isolated from the processed biscuit.